Scientific results of 30 years of CCTV research of sewer pipes - Kuliczkowski, Adam; Kuliczkowska, Emilia; Lisowska, Justyna (Instal, 2022)
The paper presents scientific achievements obtained at the Kielce University of Technology as a result of 30-year-long research on sewage pipes using the CCTV method. The research covered over 200 km of sewage pipes made in various cities in Poland. The research resulted in numerous national and international scientific papers, as well as PhD theses, monographs and a habilitation thesis